2019
DOI: 10.1007/s00265-019-2746-0
|View full text |Cite
|
Sign up to set email alerts
|

One size fits all? Relationships among group size, health, and ecology indicate a lack of an optimal group size in a wild lemur population

Abstract: Group size is a key component of sociality and can affect individual health and fitness. However, proximate links explaining this relationship remain poorly understood, partly because previous studies neglected potential confounding effects of ecological factors. Here, we correlated group size with various measures of health while controlling for measures of seasonality and habitat quality, to explore trade-offs related to group living in a mainly folivorous primate-Verreaux's sifakas (Propithecus verreauxi). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 90 publications
3
26
1
Order By: Relevance
“…Moreover, energetically costly travelling rates are associated with an increase in fGCM levels in mantled howler monkeys (Alouatta palliata; Gómez-Espinosa et al, 2014). However, daily travel distances and variation in home range size did not affect fGCM levels in Verreaux's sifakas living in the forest interior (Rudolph et al, 2019). Hence, increased fGCM levels found in the present study might be due to the lower energy intake, i.e.…”
Section: Discussioncontrasting
confidence: 59%
“…Moreover, energetically costly travelling rates are associated with an increase in fGCM levels in mantled howler monkeys (Alouatta palliata; Gómez-Espinosa et al, 2014). However, daily travel distances and variation in home range size did not affect fGCM levels in Verreaux's sifakas living in the forest interior (Rudolph et al, 2019). Hence, increased fGCM levels found in the present study might be due to the lower energy intake, i.e.…”
Section: Discussioncontrasting
confidence: 59%
“…Similar patterns were found in subsocial Anelosimus studiosus, where small groups of siblings captured more prey per capita than singletons or larger groups (Jones and Parker, 2000). It seems logical that fitness peaks at intermediate group sizes should be universal, as competition eventually overwhelms the benefits of group living (e.g., VanderWaal et al, 2009;Markham et al, 2015), yet surprisingly this is not always borne out by empirical data (Dornhaus et al, 2012;Rudolph et al, 2019). A review of colony size in social insects found that the relationship between group size and reproductive output could be positive, negative, or neutral, with no detectable intermediate peak (Dornhaus et al, 2012).…”
Section: Discussionmentioning
confidence: 68%
“…However, many species do not exhibit group sizes that conform to predictions based on ecological factors (e.g. [ 33 ]). For example, although folivores are thought to experience low within-group feeding competition, females in numerous folivorous taxa live in groups that are smaller than those found in frugivorous species (the ‘folivore paradox’ [ 34 ]; e.g.…”
Section: Introductionmentioning
confidence: 99%